The Impact of Trade Integration on Poverty Reduction in ECOWAS - Afolabi, Akinyemi Christopher; Ndamsa, Dickson Thomas (Universitas Airlangga, 2024)
This paper examines the impact of trade integration on poverty reduction in the Economic Community of West African States (ECOWAS). To investigate the impact of trade integration on poverty reduction, data for all fifteen member countries of ECOWAS on the number of poor people, bilateral trade, trade openness, exchange rate, foreign direct investment, interest rate, inflation rate, and import tariff were collected from the World Bank, WTO, IMF and WDIs from 2010 to 2019. After various tests, heteroscedasticity was found to be present. Therefore, to address this problem, the Feasible Generalized Least Squares (FGLS) method was used to examine the aforementioned impacts. The results showed that trade openness, bilateral trade, exchange rate, and import duties significantly impact poverty. The results indicated that trade integration is significant in reducing poverty within ECOWAS. The study recommends measures to enhance the effectiveness of trade integration as it has an important impact on reducing poverty in the region. First, ECOWAS should implement policies to support smaller countries in improving their productive capacities to compete effectively within the region. Secondly, harmonization of exchange rates by creating a common currency would facilitate smoother trade flows and contribute to poverty reduction. Member countries should prioritize trade with other ECOWAS nations, implement policies to ensure that foreign investments benefit the local economies, and focus on exporting finished goods rather than raw materials to create employment opportunities and support poverty reduction efforts.